The impact of joint partner decision making on obstetric choices and outcomes among Malawian women. Issue 1 (October 2016) - Rao, Nisha; Esber, Allahna; Turner, Abigail; Chilewani, Joseph; Banda, Venson; Norris, Alison
Abstract: Objective: To determine the effects of joint partner decision making on obstetric choices and outcomes in Malawi. Methods: Between July 15, 2014 and February 25, 2015, interviews were performed with women who reported at least one lifetime pregnancy in Lilongwe District, Malawi as part of a cross-sectional study of reproductive decision making. Logistic regression models were applied to examine associations of joint decision making with delivery location and obstetric complications. Results: The study population included 860 women. Women who engaged in joint decision making with partners (adjusted odds ratio [aOR] 4.9; 95% confidence interval [CI] 3.3–7.2) and women whose partners made obstetric-care decisions alone (aOR 3.2; 95% CI 2.4–4.4) were more likely to undergo delivery at a healthcare facility compared with women who made obstetric-care decisions individually. In comparison with women who made obstetric decisions individually, no difference in the likelihood of experiencing obstetric complications was observed for women who engaged in joint decision making (aOR 1.1; 95% CI 0.7–1.7) or for women whose partners made decisions individually (aOR 0.8; 95% CI 0.5–1.3). Conclusion: In rural Malawi, partner involvement in obstetric decision making was associated with improved obstetric choices.